A catologue of type material deposited in the Malacological Collections of the Museu de Ciências Naturais of Fundação Zoobotânica do Rio Grande do Sul - Heydrich, Ingrid (Arquivos de Ciências do Mar, 2017)
The Museu de Ciências Naturais of Fundação Zoobotânica do Rio Grande do Sul has two collections of mollusks. The José Willibaldo Thomé Collection started in 1955 and now has 26,000 lots, mainly collected in Rio Grande do Sul State. The Eliseo Duarte Collection, acquired in 1980, has about 20,000 lots covering five continents (the Americas, Africa, Asia, Oceania and Europe). The collections include marine, freshwater and terrestrial, recent and fossil species belonging to the classes Bivalvia, Cephalopoda, Gastropoda, Polyplacophora and Scaphopoda. One hundred and forty eight type specimens belonging to sixty six species are deposited in the collections and are listed in this paper, following the recommendations of the International Code of Zoological Nomenclature. The catalogue provides information regarding the taxon’s original name, author and publication date, family, category (holotype, paratype, topotype, syntype, paralectotype, neotype and paraneotype), type locality, collector and date, and observations.